Cross-sectional surveillance study to phenotype lorry drivers' sedentary behaviours, physical activity and cardio-metabolic health. Issue 6 (21st June 2017) - Varela-Mato, Veronica; O'Shea, Orlagh; King, James A; Yates, Thomas; Stensel, David J; Biddle, Stuart JH; Nimmo, Myra A; Clemes, Stacy A
Abstract : Objectives: Elevated risk factors for a number of chronic diseases have been identified in lorry drivers. Unhealthy lifestyle behaviours such as a lack of physical activity (PA) and high levels of sedentary behaviour (sitting) likely contribute to this elevated risk. This study behaviourally phenotyped UK lorry drivers' sedentary and non-sedentary behaviours during workdays and non-workdays and examined markers of drivers cardio-metabolic health. Setting: A transport company from the East Midlands, UK. Participants: A sample of 159 male heavy goods vehicle drivers (91% white European; (median (range)) age: 50 (24, 67) years) completed the health assessments. 87 (age: 50.0 (25.0, 65.0); body mass index (BMI): 27.7 (19.6, 43.4) kg/m 2 ) provided objective information on sedentary and non-sedentary time. Outcomes: Participants self-reported their sociodemographic information. Primary outcomes: sedentary behaviour and PA, assessed over 7 days using an activPAL3 inclinometer. Cardio-metabolic markers included: blood pressure (BP), heart rate, waist circumference (WC), hip circumference, body composition and fasted capillary blood glucose, triglycerides, high-density lipopreotein cholesterol, low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) levels. These cardio-metabolic markers were treated as secondary outcomes. Results: Lorry drivers presented an unhealthy cardio-metabolic health profile (median (IQR) systolic BP: 129 (108.5, 164) mm Hg; diastolic BP: 81 (63, 104) mm Hg; BMI: 29 (20, 47) kg/m 2 ; WC: 102 (77.5, 146.5) cm; LDL-C: 3 (1, 6) mmol/L; TC: 4.9 (3, 7.5) mmol/L). 84% were overweight or obese, 43% had type 2 diabetes or prediabetes and 34% had the metabolic syndrome. The subsample of lorry drivers with objective postural data (n=87) accumulated 13 hours/day and 8 hours/day of sedentary behaviour on workdays and non-workdays (p<0.001), respectively. On average, drivers accrued 12 min/day on workdays and 6 min/day on non-workdays of moderate-to-vigorous PA (MVPA). Conclusion: Lorry drivers demonstrate a high-risk cardio-metabolic profile and are highly sedentary and physically inactive. Interventions to reduce sitting and increase MVPA during breaks and leisure time to improve cardio-metabolic health are urgently needed. Educational programmes to raise awareness about diet and exercise are recommended.